2015
DOI: 10.1095/biolreprod.115.129411
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Adenosine Monophosphate-Activated Protein Kinase Is an Additional Mechanism That Participates in Mediating Inhibitory Actions of Prostaglandin F2Alpha in Mature, but Not Developing, Bovine Corpora Lutea1

Abstract: Elevated cytosolic calcium and protein kinase C are well-established mediators of luteolytic actions of prostaglandin F2alpha (PGF2alpha). The objectives of this study were to determine 1) if calcium/calmodulin-dependent kinase kinase 2 (CAMKK2) participates in mediating PGF2alpha actions in developing (Day [d]-4) and mature (d-10) bovine corpus luteum (CL), 2) distal targets of CAMKK2, 3) developmental expression of adenosine monophosphate-activated protein kinase (AMPK), and 4) effects of AMPK activation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…Taken together, these findings suggest that a Ca 2+ /CaMKKβ-AMPK-IRS1/PI3K/AKT signalling system mediates the amelioration of IR induced by exogenous NaHS, at least in our cell model. As reported previously, CaMKKβ and AMPK participate in signal transduction associated with the mature bovine corpus luteum 45 , in the generation of androgen-related prostate cancer and in the migration and invasion of prostate cancer 46 . In addition, the CaMKKβ-AMPK pathway also plays a role in the signalling network that regulates adipocyte development 47 .…”
Section: Discussionsupporting
confidence: 55%
“…Taken together, these findings suggest that a Ca 2+ /CaMKKβ-AMPK-IRS1/PI3K/AKT signalling system mediates the amelioration of IR induced by exogenous NaHS, at least in our cell model. As reported previously, CaMKKβ and AMPK participate in signal transduction associated with the mature bovine corpus luteum 45 , in the generation of androgen-related prostate cancer and in the migration and invasion of prostate cancer 46 . In addition, the CaMKKβ-AMPK pathway also plays a role in the signalling network that regulates adipocyte development 47 .…”
Section: Discussionsupporting
confidence: 55%
“…51 Treatment of large luteal cells with either PGF2α or PMA leads to activation of ERK signaling via PKC, 52 and ultimately apoptosis. [72][73][74] Furthermore, PGF2α actives AMPK in bovine large luteal cells, 75 which could recruit DRP1 to mitochondria. Caution is needed with this speculation because studies have demonstrated opposing effects of AMPK on DRP1, both inhibiting [76][77][78][79][80] and promoting DRP1-mediated mitochondrial fission.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the findings in cattle and rats, treatment with AICAR resulted in a significant decrease in basal P4 at all concentrations tested in experiment 1. Similarly, AICAR treatment resulted in a decrease in P4 production in the mature bovine CL [ 4 ]. This decrease in P4 could be explained, at least in part, by a decrease in key enzymes such as 3βHSD, P450scc, or StAR, all of which have been shown to be decreased after treatment with AICAR in rat granulosa cells [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…5-Aminoimidazole-4-carboxamide-1-β-4-ribofuranoside [AICAR] is a well-established, cell-permeable agent, which both directly activates AMPK alloterically and promotes phosphorylation of AMPK [ 7 ]. Treatment with AICAR (7.5 mM) significantly decreased basal P4 production in bovine CL in vitro [ 4 ]. In contrast, dorsomorphin dihydrochloride (DM) is a potent, selective, cell-permeable and reversible AMPK inhibitor [ 17 ].…”
Section: Introductionmentioning
confidence: 99%